2011
DOI: 10.1007/bf03395743
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Mental Rotation Strategies for Native Speakers of Chinese and English and How They Vary As a Function of Sex and College Major

Abstract: In this study we examine how native language, sex, and college major interact to influence accuracy and preferred strategy when performing mental rotation (MR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Furthermore, experience with character‐based languages (e.g., Mandarin), which incorporate a Euclidean frame for students learning to write, is related to higher mental rotation skill. Men and women who can write in Mandarin scored significantly higher on the MRT compared to men and women who could not write in Chinese, controlling for being multilingual …”
Section: Factors Contributing To Sex Differences In Spatial Skillmentioning
confidence: 90%
“…Furthermore, experience with character‐based languages (e.g., Mandarin), which incorporate a Euclidean frame for students learning to write, is related to higher mental rotation skill. Men and women who can write in Mandarin scored significantly higher on the MRT compared to men and women who could not write in Chinese, controlling for being multilingual …”
Section: Factors Contributing To Sex Differences In Spatial Skillmentioning
confidence: 90%
“…In this style, the user can mentally rotate the object with holistic processing and analytical processing based on some features of the object. The later studies by Li [12], [13], [14], [10], [15] noticed and concluded that the females are tending and preferring to use the combined strategy or analytical strategy.…”
Section: Combined Mental Rotationmentioning
confidence: 99%
“…Many researches by Li [12], [13], [14], [10], [15] concluded that males outperform females in a most of spatial tasks, particularly when they involve mental rotation tests. "Males tend to outperform women on spatial reasoning tests significantly.…”
Section: Gender Differencesmentioning
confidence: 99%
“…Thus, the observed female reliance on parietal lobe functioning during the EFT suggests that they are using a more spatial/holistic strategy, a notion that was contrary to our expectations and to some reports in the current literature (i.e., studies employed spatial tasks such as mental rotation, block design, etc. ), where males tend to outperform females, activate the right hemisphere and employ a predominantly spatial/holistic strategy; females, on the other hand, tend to exhibit bilateral frontal/temporal lobe activation, perhaps reflecting a more verbally mediated or combined verbal/spatial strategy (Jordan, Wüstenberg, Heinze, Peters & Jäncke, 2002;Li & O'Boyle, 2011. The aforementioned pattern found in the present study suggests that when disembedding figures, different cognitive processes and underlying neural activation are brought to bear as compared to other spatial tasks (e.g., mental rotation, block design, etc.…”
Section: Discussionmentioning
confidence: 99%
“…This sex difference in spatially ability has often been linked to the different cognitive strategies applied by males and females to visuospatial tasks (i.e., spatial versus verbally mediated). And, some recent research has shown that males and females activate different brain regions when performing the very same spatial tasks (males showing more lateralized right hemispheric activation, reflecting the use of a spatially oriented strategy and females tending towards bilateral activation, reflecting a verbally mediated or mixed spatial/verbal strategy, see Gill, O'Bovie & Hathaway, 1998;Jordan, Wüstenberg, Heinze, Peters, & Jäncke, 2002;Kucian, Loenneker, Dietrich, Martin, & Aster, 2005;Li & O'Boyle, 2011. It is important to note that most of these previous studies have employed a mental rotation task, rather than a disembedding task.…”
Section: Introductionmentioning
confidence: 97%